PELATIHAN PENERAPAN ACCURATE ACCOUNTING SOFTWARE BAGI SISWA JURUSAN AKUNTANSI DI SMK N 1 PADANG CERMIN - Heni Sulistiani; Fikri Hamidy; Suaidah Suaidah; Rika Mersita; Yunita Yunita; Yasinta Ismi HS (Universitas Teknokrat Indonesia, 2022)
The training activity on the application of Accurate Accounting Software aims to provide additional knowledge and competence in dealing with the world of work for class XII students of SMK N 1 Padang Cermin. Accurate Accounting Software is an accounting application that makes it easy for users to prepare financial reports quickly and accurately. The training method is carried out in the form of practical activities in the accounting computer laboratory of SMK N 1 Padang Cermin by solving case questions that have been prepared by the PkM team at the Indonesian Technocrat University. This training activity is carried out in three main stages: providing introductory material for Accurate Accounting Software, practical case problem solving, and discussion sessions. In the implementation of this training, the trainees were able to follow well as evidenced by the enthusiasm the trainees. In addition, the training participants are also able to solve the case questions given